Challenges in Building Interpersonal Communication Skills between Students with Academic Supervisor (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
The study aims to examine the communication patterns of students with academic supervisors in building good interpersonal communication. The impact of establishing good interpersonal communication between students and academic supervisors can increase the enthusiasm for learning and student motivation in lectures. The research subjects were students majoring in Islamic Communication and Broadcasting (KPI) Faculty of Da'wah IAIN Syekh Nurjati Cirebon. The research used is a case study-based qualitative approach. The study results indicate that the factors that encourage the establishment of good interpersonal communication between students and their supervisors include polite attitudes both through the media and when visiting the lecturer's house. Face-to-face communication and personal communication. The challenges and barriers to interpersonal communication that occurs between students and supervisors are explained by several things, namely the lack of openness in students, the way of interpersonal communication between students and lecturers, setting the guidance schedule with academic lecturers, inactivity of students in interpersonal communication with lecturers and communication patterns that are not effective.